Crystallization kinetics and fragility of a metallic glass composite. (15th January 2015) - Mukherjee, Sundeep; Arora, Harpreet Singh; Veligatla, Medha
Abstract : The crystallization behavior and viscosity of an in situ metallic glass composite was investigated using a non-contact electrostatic levitation technique. The width of the supercooled liquid region for the amorphous matrix was found to be 74 K, indicating its excellent stability against crystallization. The viscosity data follows the Vogel–Fulcher–Tammann relation, which was used to determine the fragility of the composite melt. The viscosity of the composite is compared to monolithic metallic glasses in the context of "strong-fragile" liquid behavior.